Pericardial Effusion in AIDS: Incidence and Survival - Heidenreich, Paul A.; Eisenberg, Mark J.; Kee, Laura L.; Somelofski, Carolyn A.; Hollander, Harry; Schiller, Nelson B.; Cheitlin, Melvin D. (Circulation (New York, N.Y.), 1995)
Background Although pericardial effusion is known to be common among patients infected with HIV, the incidence of pericardial effusion and its relation to survival have never been described. Methods and Results To evaluate the incidence of pericardial effusion and its relation to mortality in HIV-positive subjects, 601 echocardiograms were performed on 231 subjects recruited over a 5-year period (inception cohort: 59 subjects with asymptomatic HIV, 62 subjects with AIDS-related complex, and 74 subjects with AIDS; 21 HIV-negative healthy gay men; and 15 subjects with non-HIV end-stage medical illness). Echocardiograms were performed every 3 to 6 months (82% had follow-up studies). Sixteen subjects were diagnosed with effusions (prevalence of effusion for AIDS subjects entering the study was 5%). Thirteen subjects developed effusions during follow-up; 12 of these were subjects with AIDS (incidence, 11%/y). The majority of effusions (80%) were small and asymptomatic. The survival of AIDS subjects with effusions was significantly shorter (36% at 6 months) than survival for AIDS subjects without effusions (93% at 6 months). This shortened survival remained significant (relative risk, 2.2, P =.01) after adjustment for lead time bias and was independent of CD4 count and albumin level. Conclusions There is a high incidence of pericardial effusion in patients with AIDS, and the presence of an effusion is associated with shortened survival. The development of an effusion in the setting of HIV infection suggests end-stage HIV disease (AIDS).